Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Effect of Drought and Heavy Precipitation on CH4 Emissions and δ13C–CH4 in a Northern Temperate Peatland - Clarice R. Perryman; Carmody K. McCalley; Joanne H. Shorter; Apryl L. Perry; Natalie White; Angelica Dziurzynski; Ruth K. Varner (Ecosystems, 2024)

Nutrients Alter Methane Production and Oxidation in a Thawing Permafrost Mire - N. Niloufar Kashi; Erik A. Hobbie; Ruth K. Varner; Adam S. Wymore; Jessica G. Ernakovich; Reiner Giesler (Ecosystems, 2023)

The Ocean as a Classroom: Considering the Roles of Equity, Diversity, and Justice in Oceanographic Knowledge Production to Promote Accessibility for Future Generations - Natalia Erazo; Tricia Light; Dante Capone; Anna Effinger; Pierina Erazo; Linqing Huang; Ankitha Kannad; Kaycie Lanpher; Emmet Norris; Shannon Perry; Emilio Romero; Tamara Russell; et al. (Oceanography, 2023)
Understanding the history of how we studied our ocean in the past and how we study it now will help us develop approaches to make future oceanographic knowledge production more diverse, accessible, and inclusive. The motto of the UN Decade of Ocean Science for Sustainable Development (2021–2030) is, “The ocean we need for the future we want” (Singh et al., 2021). The Ocean Decade gives the ocean sciences community an opportunity to change the way it conducts research, to use ocean science to support sustainable development, and to energize the ocean sciences for future generations. With these goals in mind, we developed an introductory level, student-led graduate seminar that builds on the Ocean Decade framework. A research cruise involving seminar participants followed the seminar sessions. Here, we discuss how we conducted the seminar and highlight directions that are needed to energize future generations of ocean leaders and make ocean science more equitable, inclusive, and accessible.

Coupling plant litter quantity to a novel metric for litter quality explains C storage changes in a thawing permafrost peatland - Moira Hough; Samantha McCabe; S. Rose Vining; Emily Pickering Pedersen; Rachel M. Wilson; Ryan Lawrence; Kuang‐Yu Chang; Gil Bohrer; William J. Riley; Patrick M. Crill; Ruth K. Varner; Steven J. Blazewicz; et al. (Global Change Biology, 2022)
Permafrost thaw is a major potential feedback source to climate change as it can drive the increased release of greenhouse gases carbon dioxide (CO 2 ) and methane (CH 4 ). This carbon release from the decomposition of thawing soil organic material can be mitigated by increased net primary productivity (NPP) caused by warming, increasing atmospheric CO 2 , and plant community transition. However, the net effect on C storage also depends on how these plant community changes alter plant litter quantity, quality, and decomposition rates. Predicting decomposition rates based on litter quality remains challenging, but a promising new way forward is to incorporate measures of the energetic favorability to soil microbes of plant biomass decomposition. We asked how the variation in one such measure, the nominal oxidation state of carbon (NOSC), interacts with changing quantities of plant material inputs to influence the net C balance of a thawing permafrost peatland. We found: (1) Plant productivity (NPP) increased post‐thaw, but instead of contributing to increased standing biomass, it increased plant biomass turnover via increased litter inputs to soil; (2) Plant litter thermodynamic favorability (NOSC) and decomposition rate both increased post‐thaw, despite limited changes in bulk C:N ratios; (3) these increases caused the higher NPP to cycle more rapidly through both plants and soil, contributing to higher CO 2 and CH 4 fluxes from decomposition. Thus, the increased C‐storage expected from higher productivity was limited and the high global warming potential of CH 4 contributed a net positive warming effect. Although post‐thaw peatlands are currently C sinks due to high NPP offsetting high CO 2 release, this status is very sensitive to the plant community's litter input rate and quality. Integration of novel bioavailability metrics based on litter chemistry, including NOSC, into studies of ecosystem dynamics, is needed to improve the understanding of controls on arctic C stocks under continued ecosystem transition.

Spatial and temporal heterogeneity of methane ebullition in lowland headwater streams and the impact on sampling design - Andrew L. Robison; Wilfred M. Wollheim; Bonnie Turek; Cynthia Bova; Carter Snay; Ruth K. Varner (Limnology and Oceanography, 2021)
Headwater streams are known sources of methane (CH 4 ) to the atmosphere, but their contribution to global scale budgets remains poorly constrained. While efforts have been made to better understand diffusive fluxes of CH 4 in streams, much less attention has been paid to ebullitive fluxes. We examine the temporal and spatial heterogeneity of CH 4 ebullition from four lowland headwater streams in the temperate northeastern United States over a 2‐yr period. Ebullition was observed in all monitored streams with an overall mean rate of 1.00 ± 0.23 mmol CH 4 m −2 d −1 , ranging from 0.01 to 1.79 to mmol CH 4 m −2 d −1 across streams. At biweekly timescales, rates of ebullition tended to increase with temperature. We observed a high degree of spatial heterogeneity in CH 4 ebullition within and across streams. Yet, catchment land use was not a simple predictor of this heterogeneity, and instead patches scale variability weakly explained by water depth and sediment organic matter content and quality. Overall, our results support the prevalence of CH 4 ebullition from streams and high levels of variability characteristic of this process. Our findings also highlight the need for robust temporal and spatial sampling of ebullition in lotic ecosystems to account for this high level of heterogeneity, where multiple sampling locations and times are necessary to accurately represent the mean rate of flux in a stream. The heterogeneity observed likely indicates a complex set of drivers affect CH 4 ebullition from streams which must be considered when upscaling site measurements to larger spatial scales.

Divergent Controls on Stream Greenhouse Gas Concentrations Across a Land-Use Gradient - Allison M. Herreid; Adam S. Wymore; Ruth K. Varner; Jody D. Potter; William H. McDowell (Ecosystems, 2021)

The missing pieces for better future predictions in subarctic ecosystems: A Torneträsk case study - Didac Pascual; Jonas Åkerman; Marina Becher; Terry V. Callaghan; Torben R. Christensen; Ellen Dorrepaal; Urban Emanuelsson; Reiner Giesler; Dan Hammarlund; Edward Hanna; Annika Hofgaard; Hongxiao Jin; et al. (Ambio, 2021)
Arctic and subarctic ecosystems are experiencing substantial changes in hydrology, vegetation, permafrost conditions, and carbon cycling, in response to climatic change and other anthropogenic drivers, and these changes are likely to continue over this century. The total magnitude of these changes results from multiple interactions among these drivers. Field measurements can address the overall responses to different changing drivers, but are less capable of quantifying the interactions among them. Currently, a comprehensive assessment of the drivers of ecosystem changes, and the magnitude of their direct and indirect impacts on subarctic ecosystems, is missing. The Torneträsk area, in the Swedish subarctic, has an unrivalled history of environmental observation over 100 years, and is one of the most studied sites in the Arctic. In this study, we summarize and rank the drivers of ecosystem change in the Torneträsk area, and propose research priorities identified, by expert assessment, to improve predictions of ecosystem changes. The research priorities identified include understanding impacts on ecosystems brought on by altered frequency and intensity of winter warming events, evapotranspiration rates, rainfall, duration of snow cover and lake-ice, changed soil moisture, and droughts. This case study can help us understand the ongoing ecosystem changes occurring in the Torneträsk area, and contribute to improve predictions of future ecosystem changes at a larger scale. This understanding will provide the basis for the future mitigation and adaptation plans needed in a changing climate.

Evidence for non‐methanogenic metabolisms in globally distributed archaeal clades basal to the Methanomassiliicoccales - Laura A. Zinke; Paul N. Evans; Christian Santos‐Medellín; Alena L. Schroeder; Donovan H. Parks; Ruth K. Varner; Virginia I. Rich; Gene W. Tyson; Joanne B. Emerson (Environmental Microbiology, 2021)
Summary Recent discoveries of mcr and mcr ‐like genes in genomes from diverse archaeal lineages suggest that methane metabolism is an ancient pathway with a complicated evolutionary history. One conventional view is that methanogenesis is an ancestral metabolism of the class Thermoplasmata . Through comparative genomic analysis of 12 Thermoplasmata metagenome‐assembled genomes (MAGs) basal to the Methanomassiliicoccales , we show that these microorganisms do not encode the genes required for methanogenesis. Further analysis of 770 Ca . Thermoplasmatota genomes/MAGs found no evidence of mcrA homologues outside of the Methanomassiliicoccales . Together, these results suggest that methanogenesis was laterally acquired by an ancestor of the Methanomassiliicoccales . The 12 analysed MAGs include representatives from four orders basal to the Methanomassiliicoccales , including a high‐quality MAG that likely represents a new order, Ca . Lunaplasma lacustris ord. nov. sp. nov. These MAGs are predicted to use diverse energy conservation pathways, including heterotrophy, sulfur and hydrogen metabolism, denitrification, and fermentation. Two lineages are widespread among anoxic, sedimentary environments, whereas Ca . Lunaplasma lacustris has thus far only been detected in alpine caves and subarctic lake sediments. These findings advance our understanding of the metabolic potential, ecology, and global distribution of the Thermoplasmata and provide insight into the evolutionary history of methanogenesis within the Ca . Thermoplasmatota.

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Endogenous circadian regulation of carbon dioxide exchange in terrestrial ecosystems - Víctor Resco de Dios; Michael L. Goulden; Kiona Ogle; Andrew D. Richardson; David Y. Hollinger; Eric A. Davidson; Josu G. Alday; Greg A. Barron‐Gafford; Arnaud Carrara; Andrew S. Kowalski; Walt C. Oechel; Borja R. Reverter; et al. (Global Change Biology, 2012)
It is often assumed that daytime patterns of ecosystem carbon assimilation are mostly driven by direct physiological responses to exogenous environmental cues. Under limited environmental variability, little variation in carbon assimilation should thus be expected unless endogenous plant controls on carbon assimilation, which regulate photosynthesis in time, are active. We evaluated this assumption with eddy flux data, and we selected periods when net ecosystem exchange ( NEE ) was decoupled from environmental variability in seven sites from highly contrasting biomes across a 74° latitudinal gradient over a total of 36 site‐years. Under relatively constant conditions of light, temperature, and other environmental factors, significant diurnal NEE oscillations were observed at six sites, where daily NEE variation was between 20% and 90% of that under variable environmental conditions. These results are consistent with fluctuations driven by the circadian clock and other endogenous processes. Our results open a promising avenue of research for a more complete understanding of ecosystem fluxes that integrates from cellular to ecosystem processes.

Fine root dynamics and trace gas fluxes in two lowland tropical forest soils - Whendee L. Silver; Andrew W. Thompson; Megan E. McGroddy; Ruth K. Varner; Jadson D. Dias; Hudson Silva; Patrick M. Crill; Michael Keller (Global Change Biology, 2005)
Fine root dynamics have the potential to contribute significantly to ecosystem‐scale biogeochemical cycling, including the production and emission of greenhouse gases. This is particularly true in tropical forests which are often characterized as having large fine root biomass and rapid rates of root production and decomposition. We examined patterns in fine root dynamics on two soil types in a lowland moist Amazonian forest, and determined the effect of root decay on rates of C and N trace gas fluxes. Root production averaged 229 (±35) and 153 (±27) g m −2 yr −1 for years 1 and 2 of the study, respectively, and did not vary significantly with soil texture. Root decay was sensitive to soil texture with faster rates in the clay soil ( k =−0.96 year −1 ) than in the sandy loam soil ( k =−0.61 year −1 ), leading to greater standing stocks of dead roots in the sandy loam. Rates of nitrous oxide (N 2 O) emissions were significantly greater in the clay soil (13±1 ng N cm −2 h −1 ) than in the sandy loam (1.4±0.2 ng N cm −2 h −1 ). Root mortality and decay following trenching doubled rates of N 2 O emissions in the clay and tripled them in sandy loam over a 1‐year period. Trenching also increased nitric oxide fluxes, which were greater in the sandy loam than in the clay. We used trenching (clay only) and a mass balance approach to estimate the root contribution to soil respiration. In clay soil root respiration was 264–380 g C m −2 yr −1 , accounting for 24% to 35% of the total soil CO 2 efflux. Estimates were similar using both approaches. In sandy loam, root respiration rates were slightly higher and more variable (521±206 g C m 2 yr −1 ) and contributed 35% of the total soil respiration. Our results show that soil heterotrophs strongly dominate soil respiration in this forest, regardless of soil texture. Our results also suggest that fine root mortality and decomposition associated with disturbance and land‐use change can contribute significantly to increased rates of nitrogen trace gas emissions.